Analisis Faktor – Faktor Yang Mempengaruhi Pendapatan Usahatani Sawi (Brassica Juncea L) di Kelurahan Landasan Ulin Utara Kecamatan Lianganggang Kota Banjarbaru - Beronaputri, Vasella; Chandriyanti, Ika (PPJP ULM, 2023)
The research was conducted to understand the elements contained in mustard farming income, which consists of several components, namely land area, production amount, and green mustard price partially and simultaneously that, using multiple linear regression analysis and using classical assumption tests and hypothesis tests. The research location is in North Landasan Ulin Village, with 80 farmers as respondents, and the sample selection uses the Simple Random Sampling technique. The research results for the variable land area have a positive and insignificant effect on the income of green mustard farming in North Landasan Ulin Village. Meanwhile, the amount of production and the price of mustard greens are positive and significant to the payment of green mustard plant farming in the North Landasan Ulin platform. The result of the coefficient of determination (R2) is 0.9765, where the change in income up and down (Y) is explained by the area of land (X1), the amount of production (X2), and the price of mustard greens (X3) as much as 97.65%. In comparison, the remaining 2.35% is explained apart from variables that don’t exist in the study.